Enhanced Growth Potential of Tilapia (Oreochromis niloticus) Through Maggot-Based Feeding in Multi-Trophic Systems - Heriansah, Heriansah; Fathuddin; Nursidi, Nursidi; Izzul Alfarifdy, Muh. (Department of Aquaculture, 2024)
Highly nutritious insects, such as black soldier fly (BSF) larvae, also referred toas maggot, have been evaluated as feed in monoculture systems, but their use in multi-trophic systems has not been previously investigated. This study used maggot-based feed in a multi-trophic system on a laboratory scale to evaluate the survival and growth performance of tilapia (Oreochromis niloticus). Tilapia were cocultured with freshwater lobster, freshwater clams, and paddy. Four experimental diets were used including a commercial pellet as a control (CP), live maggots (LM), dried maggots (DM), and supplemented maggots (SM). Tilapia (initial weight, 4.1 ± 0.2 g) and other organisms were reared in plastic tanks (water volume 50 L) and randomly distributed into 12 tanks, each containing 20 individual tilapia. The experimental diets were given four times a day at a feeding rate of 10% tilapia biomass. After 28 days of feeding, the survival and growth of tilapia on the CP diet were 90.0% and 2.8% day-1, LM 93.3% and 2.7% day-1, DM 93.3% and 3.3% day-1, and SM 90.0% and 3.1% day-1, respectively. There was no significant effect (P > 0.05) on the survival performance among the experimental diets. However, the growth confirmed by Specific Growth Rate (SGR) showed a significant effect (P < 0.05). SGR values were found to be significantly higher in the DM and SM diets than in the CP diet. An important finding of this research is the potential of maggot-based feed to increase the growth of tilapia in multi-trophic systems without impairing their survival.